Preparation method of cerium dioxide coated gold-palladium bimetallic nano cuboid composite material
By coating ceria on the surface of the gold-palladium bimetallic nanoclip, the problem of easy deactivation and fall off of precious metals is solved, the stability and efficiency of the photocatalyst is improved, and the effective degradation of organic pollutants is achieved.
Patent Information
- Application Number
- CN202411665483.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
The existing photocatalysts are easily deactivated and fall off due to the low photocatalytic efficiency of a single semiconductor material, resulting in limited application.
The preparation method of core-shell gold-palladium bimetallic nanoclip/ceria composite material is adopted. By coating ceria on the surface of the gold-palladium bimetallic nanoclip, the slow hydrolysis of ceria is promoted by ethylenediaminetetraacetic acid, ensuring uniform adhesion of ceria and forming a stable structure.
It improves the utilization efficiency of precious metals and ceria, enhances the stability and photocatalytic activity of the photocatalyst, and can effectively degrade organic pollutants.
Smart Images

Figure CN119500124A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a ceria-coated gold-palladium bimetallic nanocuboid composite material, belonging to the field of composite materials. Background Art
[0002] Photocatalysts are substances that use light sources such as sunlight to generate electron-hole pairs for catalytic action. The generated electrons are reducing and the generated holes are oxidizing, which is conducive to the redox reaction. They have a wide range of application potentials in sterilization, splitting water to produce hydrogen and oxygen, as well as heavy metal reduction and organic matter decomposition.
[0003] In 1972, Japanese scientists Akira Fujishima and Kenichi Honda first discovered that titanium dioxide (TiO2) can decompose water under ultraviolet light. Titanium dioxide, as a new material, has attracted people's attention. However, the excitation light source of titanium dioxide is in the ultraviolet light band, and the ultraviolet light energy in sunlight only accounts for about 5% of the total energy of solar radiation, which greatly restricts the application of titanium dioxide photocatalysts. In recent years, cerium dioxide, a compound of cerium, the most abundant element among rare earth elements, has attracted widespread attention. Cerium dioxide is even more abundant in my country, and cerium dioxide has higher catalytic activity, better chemical stability, non-toxicity, and simple preparation method, making it a new type of photocatalytic material and attracting much attention.
[0004] At present, most single-type semiconductor materials have problems such as high recombination rate of photogenerated electrons and holes, poor absorption rate of visible light, low photocatalytic efficiency, and low quantum yield. Gold and silver in precious metal materials not only have unique localized plasma resonance effects, but also have good electron-hole separation capabilities. Therefore, the study of precious metal / semiconductor composite photocatalysts has important research significance and application value.
[0005] Among the research methods reported so far, it is common to form a composite structure by coating precious metals such as gold, silver, palladium and other materials on the surface of semiconductor materials such as cerium dioxide. However, since gold, silver and palladium are exposed on the outer surface of the composite structure, it is easy to cause problems such as inactivation and shedding of precious metals, and the cost of the precious metal materials themselves is high. Therefore, we adopted a composite structure in which gold, silver and palladium precious metal nanomaterials are first synthesized and then coated with semiconductor cerium dioxide. In addition, directly coating semiconductors such as cerium dioxide on the surface of precious metals such as gold, silver and palladium often has problems such as lattice mismatch. By promoting the slow hydrolysis of cerium nitrate by ethylenediaminetetraacetic acid, cerium dioxide can be well attached to the surface of precious metals. After high-temperature drying, the gold-palladium rectangular nanostructure coated with cerium dioxide has better stability. Summary of the invention
[0006] In order to solve the problems existing in the existing materials, the present invention provides a method for preparing a ceria-coated gold-palladium bimetallic nanocuboid composite material. The structure of the core-shell type gold-palladium bimetallic nanocuboid / ceria composite material is: the gold-palladium bimetallic nanocuboid composite structure is used as the core, and ceria is used as the shell layer. The specific preparation method comprises the following steps:
[0007] (1) Hexadecyltrimethylammonium bromide, sodium oleate and ultrapure water are mixed and heated until all solids are dissolved to obtain a transparent colorless growth solution I.
[0008] (2) After cooling the growth solution I obtained in step (1), silver nitrate solution and chloroauric acid solution are added in sequence, and stirred at a constant temperature to obtain a mixed solution.
[0009] (3) adding sodium borohydride solution and chloroauric acid solution to hexadecyltrimethylammonium bromide solution in sequence, reacting in an ice bath to obtain a gold seed solution, and aging the gold seed solution to obtain gold seeds required for synthesizing gold nanorods.
[0010] (4) adding hydrochloric acid, ascorbic acid solution and the gold seeds obtained in step (3) in sequence to the mixed solution obtained in step (2) under stirring; after all the additions are completed, the mixture is allowed to stand at a constant temperature to form a gold nanorod stock solution; the gold nanorod stock solution is centrifuged to obtain a precipitate; and ultrapure water is added to the precipitate to obtain a gold nanorod concentrated solution.
[0011] (5) The hexadecyltrimethylammonium bromide solution, the ascorbic acid solution and the gold nanorod concentrate obtained in step (4) are mixed at a constant temperature to prepare growth solution II.
[0012] (6) Adding sodium chloropalladate solution to growth solution II, stirring at a constant temperature and then standing to obtain a gold-palladium bimetallic nanocuboid composite structure stock solution, centrifuging the gold-palladium bimetallic nanocuboid composite structure stock solution, retaining the precipitate, and adding ultrapure water to the precipitate to obtain a gold-palladium bimetallic nanocuboid composite structure concentrated solution.
[0013] (7) Adding ethylenediaminetetraacetic acid solution and cerium nitrate solution to the concentrated solution of gold-palladium bimetallic nanocuboid composite structure obtained in step (6) in sequence, and drying the obtained mixed solution to obtain cerium dioxide-coated gold-palladium bimetallic nanocuboid composite material.
[0014] Preferably, in the ultrapure water of step (1), the amount of cetyltrimethylammonium bromide added is 9.1-37 g / L, the amount of sodium oleate added is 1-10 g / L, the molar ratio of cetyltrimethylammonium bromide to sodium oleate is 1:1-1:2, and the heating temperature is 30-90°C.
[0015] Preferably, in step (2), the volume ratio of the growth solution I, the silver nitrate solution and the chloroauric acid solution is: (5-25): (1-4): (10-50); the molar concentration of the silver nitrate solution is 4-40 mmol / L, and the molar concentration of the chloroauric acid solution is 1-5 mmol / L; the temperature of the growth solution I after cooling is 20-40°C; the temperature of the constant temperature stirring is 20-40°C, the stirring condition is 200-1000 r / min, and the stirring is 10-150 min.
[0016] Preferably, in step (3), the volume ratio of the sodium borohydride solution, the chloroauric acid solution and the hexadecyltrimethylammonium bromide solution is 1:5:5, wherein the molar concentration of the sodium borohydride solution is 6 mmol / L, the molar concentration of the chloroauric acid solution is 0.5 mmol / L, and the molar concentration of the hexadecyltrimethylammonium bromide solution is 0.2 mol / L; the aging temperature is 25-50° C., and the aging time is more than 30 min.
[0017] Preferably, in step (4), the amount of hydrochloric acid added to the mixed solution is 1-5 μL / ml, the amount of ascorbic acid solution added is 1-5 μL / ml, and the amount of gold seeds added is 0.35-1.4 μL / ml; the mass concentration of the hydrochloric acid is 37%, and the molar concentration of the ascorbic acid solution is 64-100 mmol / L.
[0018] Preferably, in step (4), each reagent needs to be stirred for more than 30 seconds after addition, and the constant temperature is 20-40°C for a standing time of more than 12 hours; centrifugation is performed twice, and the centrifugation conditions are 6000-12000r / min for 2-10 minutes, and the supernatant is removed after each centrifugation to collect the precipitate; the amount of ultrapure water used in the precipitate is 1 / 10th of the volume of the gold nanorod stock solution. times.
[0019] Preferably, the volume ratio of the hexadecyltrimethylammonium bromide solution, the ascorbic acid solution and the gold nanorod concentrate in the growth solution II of step (5) is (0.2-2):(0.2-2):(0.2-2), the molar concentration of the hexadecyltrimethylammonium bromide is 0.1-0.2 mol / L, and the molar concentration of the ascorbic acid is 0.064-0.1 mol / L; and the constant temperature condition is 30°C.
[0020] Preferably, in step (6), the amount of sodium chloropalladate solution added to the growth solution II is 16.7-50 μL / ml, the molar concentration of the sodium chloropalladate solution is 1-10 mmol / L, the constant temperature condition is 30° C., the stirring time is 5-10 min, and the standing time is 6-20 h.
[0021] Preferably, in step (6), the centrifugation condition is 4000-10000r / min for 3-10min, and the amount of ultrapure water added to the precipitate is 1 / 10 of the volume of the gold-palladium bimetallic nanocuboid composite structure stock solution. times.
[0022] Preferably, in step (7), the volume ratio of the gold-palladium bimetallic nanocuboid composite structure concentrated solution, the ethylenediaminetetraacetic acid solution and the cerium nitrate solution is 1:3.5:0.035-1:7:0.70, the molar concentration of the ethylenediaminetetraacetic acid solution is 1-10 mmol / L, and the molar concentration of the cerium nitrate solution is 10-100 mmol / L; the drying condition is 90-100°C and the drying time is 2-10 h.
[0023] The invention discloses an application of a ceria-coated gold-palladium bimetallic nanocuboid composite structure prepared by the method of the invention in the degradation of methylene blue.
[0024] Beneficial effects of the present invention
[0025] (1) The composite nanostructure prepared by the present invention combines the advantages of high absorption rate of precious metals such as gold and palladium in the visible light band and high photocatalytic efficiency of semiconductor cerium dioxide. Compared with single precious metal nanostructures, the gold-palladium bimetallic nanostructure has a stronger ability to store photogenerated electrons. At the same time, since cerium dioxide is coated on the outer layer, it can effectively prevent the problems of inactivation and shedding of precious metals, save the amount of precious metal gold and palladium, and improve the utilization efficiency of precious metals and cerium dioxide.
[0026] (2) The present invention closely attaches the palladium nanoparticle shell to the surface of the gold nanorod by epitaxial growth, so that the chemical potential of the gold nanorod and the palladium nanoparticle is in a stable state. Therefore, when the material obtains the excitation energy of visible light, it not only stimulates the plasma resonance effect of the gold nanorod, but also promotes the catalytic activity of the palladium nanoparticle.
[0027] (3) Under the irradiation of simulated sunlight, the composite nano-photocatalyst can effectively degrade the organic pollutant methylene blue, indicating that it has excellent photocatalytic activity and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the process of synthesizing Au@Pd@CeO2 NRs in the present invention.
[0029] Figure 2 Transmission electron microscope (TEM) images and ultraviolet-visible (UV-vis) spectra of gold nanorods (Au NRs) prepared by the present invention.
[0030] Figure 3Transmission electron microscope (TEM) images, elemental analysis diagrams (Mapping), ultraviolet-visible (UV-vis) spectra and line profiles (Line Profile) of the gold-palladium bimetallic nanocuboid composite structure (Au@Pd NCBs) prepared by the present invention.
[0031] Figure 4 Transmission electron microscope (TEM) images, elemental analysis diagram (Mapping), line scan elemental analysis diagram (LineProfile) and ultraviolet-visible (UV-vis) spectrum diagram of the cerium dioxide-coated gold-palladium bimetallic nanocuboid composite material (Au@Pd@CeO2 NCBs) prepared by the present invention.
[0032] Figure 5 The photocatalytic degradation effect diagram of the gold nanorods (Au NRs), gold-palladium bimetallic nanocuboid composite structures (Au@Pd NCBs) and ceria-coated gold-palladium bimetallic nanocuboid composite materials (Au@Pd@CeO2 NCBs) prepared in the present invention on methylene blue before and after drying. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0034] Example 1
[0035] A method for preparing a core-shell gold-palladium bimetallic nanocuboid / cerium dioxide composite material, specifically comprising the following steps:
[0036] (1) 0.91 g of hexadecyltrimethylammonium bromide (CTAB), 0.1234 g of sodium oleate (NaOL) and 25 mL of ultrapure water were mixed and heated to 60° C. to dissolve the solids completely, obtaining 25 mL of a transparent, colorless growth solution I;
[0037] (2) After cooling the growth solution I prepared in step (1) to 30° C., 2.4 mL of 4 mmol / L silver nitrate solution (AgNO3) and 30 mL of 1 mmol / L chloroauric acid solution (HAuCl4) were added in sequence, and then maintained at 30° C. and 700 rpm for 90 minutes to obtain a mixed solution.
[0038] (3) 1 ml of 6 mmol / L sodium borohydride solution was added to 5 ml of 0.5 mmol / L chloroauric acid solution and 5 ml of 0.2 mol / L hexadecyltrimethylammonium bromide solution, and the mixture was evenly mixed. The mixture was reacted in an ice bath to obtain a gold seed solution. The gold seed solution was aged at 30°C for 30 min to obtain the gold seeds required for synthesizing gold nanorods.
[0039] (4) At a rotation speed of 400 r / min, 190 μL of 37% hydrochloric acid (HCl), 150 μL of 64 mmol / L ascorbic acid solution (AA) and the gold seeds prepared in step (3) were added to the mixed solution obtained in step (2) in sequence. Four different gold nanorod stock solutions were prepared by changing the amount of gold seeds added. The amount of gold seeds added was 20 μL, 40 μL, 60 μL and 80 μL, respectively. After each solution was added in sequence, it was stirred at 400 rpm for 30 seconds before adding the next solution. After all the solutions were added, they were allowed to stand at 30° C. for 12 hours to form a uniform and stable gold nanorod stock solution. The solution was then centrifuged twice, at 7000 rpm for 5 minutes and at 6000 rpm for 6 minutes. During the two centrifugations, the supernatant needed to be removed to remove excess hexadecyltrimethylammonium bromide to obtain a precipitate of gold nanorods. Ultrapure water was added to the precipitate of the gold nanorods to obtain Au There are four kinds of gold nanorod concentrates, namely Au NRs-20, Au NRs-40, Au NRs-60 and Au NRs-80. The amount of ultrapure water used is 1 / 2 of the volume of the gold nanorod stock solution. times.
[0040] (5) At 30°C, 2 mL of Au NRs-80 gold nanorod concentrate, 2 mL of 0.1 mol / L hexadecyltrimethylammonium bromide solution, and 2 mL of 0.1 mol / L ascorbic acid solution were mixed to obtain growth solution II.
[0041] (6) Add 2 mmol / L sodium chloropalladate solution (Na2PdCl4) to the growth solution II obtained in step (5), stir vigorously at 30°C for 10 minutes and then stand at 30°C for 14 hours to obtain a gold-palladium bimetallic nanocube structure stock solution (Au@Pd NCBs). By changing the amount of sodium chloropalladate solution (Na2PdCl4) added, three different gold-palladium bimetallic nanocube composite structure stock solutions were prepared. The amounts of sodium chloropalladate solution (Na2PdCl4) added were 100 μL, 200 μL, and 300 μL, respectively, to obtain gold-palladium bimetallic nanocube composite structure stock solutions coated with different palladium thicknesses. The gold-palladium bimetallic nanocuboid composite structure stock solution was centrifuged at 5000 rpm for 5 min, the supernatant was removed and the precipitate was retained, and ultrapure water was added to the precipitate to obtain three kinds of gold-palladium bimetallic nanocuboid composite structure concentrated solutions, namely Au@PdNCBs-100, Au@Pd NCBs-200 and Au@Pd NCBs-300, wherein the amount of ultrapure water added was 1 / 100 of the volume of the gold-palladium bimetallic nanocuboid composite structure stock solution. times.
[0042] (7) Add 1 mL of the concentrated Au@Pd 10mmol / L ethylenediaminetetraacetic acid solution (EDTA) and 100mmol / L cerium nitrate solution (Ce(NO3)3) were added to the concentrated solution of NCBs-200 gold-palladium bimetallic nanocuboid composite structure in sequence, and the mixture was dried at 90°C for 4h to obtain cerium dioxide-coated gold-palladium bimetallic nanocuboid composite material (Au@Pd@CeO2NCBs). Two different cerium dioxide-coated gold-palladium bimetallic nanocuboid composite structures were prepared by controlling the added amount of ethylenediaminetetraacetic acid solution (EDTA) and cerium nitrate solution (Ce(NO3)3). When the added amount of ethylenediaminetetraacetic acid solution (EDTA) was 7mL and the added amount of cerium nitrate solution (Ce(NO3)3) was 0.14mL, that is, the molar ratio of EDTA to Ce(NO3)3 was 5:1, the prepared material was Au@Pd@CeO2NCBs-5; when When the amount of EDTA added was 7 mL and the amount of cerium nitrate solution (Ce(NO3)3) added was 0.07 mL, i.e., the molar ratio of EDTA to Ce(NO3)3 was 10:1, the prepared material was Au@Pd@CeO2NCBs-10; when the amount of EDTA added was 7 mL and the amount of cerium nitrate solution (Ce(NO3)3) added was 0.35 mL, That is, when the molar ratio of EDTA to Ce(NO3)3 is 2:1, the prepared material is Au@Pd@CeO2NCBs-2; when the added amount of ethylenediaminetetraacetic acid (EDTA) is 7 mL and the added amount of cerium nitrate (Ce(NO3)3) is 0.7 mL, that is, when the molar ratio of EDTA to Ce(NO3)3 is 1:1, the prepared material is Au@Pd@CeO2NCBs-1.
[0043] Figure 1 The whole process of synthesizing Au@Pd@CeO2NRs using gold nanorods (AuNRs) as seeds is shown.
[0044] Figure 2 The transmission electron microscope (TEM) image and ultraviolet-visible (UV-vis) spectrum of the gold nanorod concentrate Au NRs obtained in step (4) are shown. Figure 2 (a) and (b) are the TEM images and UV-vis spectra of the gold nanorod concentrate Au NRs-80, respectively. It can be seen that the prepared gold nanorods have two plasma resonance peaks in the longitudinal and transverse directions, with the longitudinal peak at 880nm and the transverse peak at 505nm. Figure 2(c)-(f) are TEM images and UV-vis spectra of gold nanorod concentrates Au NRs-20, Au NRs-40, and Au NRs-60 obtained by reducing the amount of gold seeds added. It can be seen that the longitudinal peaks of the three gold nanorod concentrates are at 695nm, 667nm, and 651nm, respectively, and the transverse peaks are at 513nm, 516nm, and 520nm, respectively.
[0045] Figure 3 The transmission electron microscope (TEM) image, elemental analysis diagram (Mapping), ultraviolet-visible (UV-vis) spectrum diagram and line scan elemental analysis diagram (LineProfile) of the gold-palladium bimetallic nanocube composite structure (Au@Pd NCBs) prepared in step (6) are shown. Figure 3 (a) and (b) are TEM images of Au@PdNCBs-200, a gold-palladium bimetallic nanocuboid composite structure concentrate. Figure 3 (c) and (d) are TEM images of Au@PdNCBs-100 and Au@Pd NCBs-300, respectively. Figure 3 (e)-(h) are the mapping characterization images of Au@Pd NCBs-200, a concentrated solution of Au@Pd bimetallic nanocuboid composite structure. It can be seen that the Pd nanoparticles are evenly coated on the surface of the gold nanorods. Figure 3 (i) is a comparison of the UV-vis spectra of Au@Pd NCBs-200, a gold-palladium bimetallic nanocuboid composite structure concentrate, and AuNRs-80, a gold nanorod concentrate. It can be seen that the transverse plasma peak position does not change before and after coating, and the longitudinal plasma peak position red-shifts from 855nm to 885nm. In addition, since the surface plasmon effect of Pd nanoparticles is not as strong as that of Au NRs, the absorption value also decreases. Figure 3 (j) is the LineProfile analysis of the Au@Pd NCBs-200 concentrated solution of the gold-palladium bimetallic nanocuboid composite structure. The distribution of the Pd element content can further prove that the palladium nanoparticles are evenly coated on the surface of the gold nanorods.
[0046] Figure 4 The transmission electron microscope (TEM) image, elemental analysis diagram (Mapping), line scan elemental analysis diagram (LineProfile) and ultraviolet-visible (UV-vis) spectrum diagram of the cerium dioxide-coated gold-palladium bimetallic nanocube composite material (Au@Pd@CeO2 NCBs) prepared in step (7) are shown. Figure 4 (a)-(b) are TEM images of Au@Pd@CeO2NCBs-5. Figure 4(c)-(h) are the mapping characterization images of Au@Pd@CeO2NCBs-5. It can be seen that CeO2 is coated on the surface of Au@Pd NCBs. Figure 4 (i) Line Profile analysis of Au@Pd@CeO2NCBs-5. The content distribution analysis of Ce element further proves that CeO2 is coated on the surface of gold nanorods. Figure 4 (j) is the comparison of UV-vis spectra of Au@Pd@CeO2NCBs-5 and Au@Pd NCBs-200. It can be seen that the positions of both longitudinal and transverse plasma peaks have not changed before and after coating. However, due to the coating of CeO2, the plasmon effect of the material is further reduced, and the absorption value is further reduced. Figure 4 (k), (l), and (m) are TEM images of Au@Pd@CeO2NCBs-10, Au@Pd@CeO2NCBs-2, and Au@Pd@CeO2NCBs-1, respectively. It can be clearly seen that with the change of the ratio of EDTA to Ce(NO3)3, the CeO2 content in the environment around the AuPd nanoparticles increases, and Figure 4 The excessive CeO2 content in (m) resulted in CeO2 not growing along the surface of Au@Pd NCBs but growing alone. Figure 4 (n) is the UV-vis spectra of Au@Pd@CeO2 NCBs-5, Au@Pd@CeO2 NCBs-10, Au@Pd@CeO2 NCBs-2, and Au@Pd@CeO2 NCBs-1. It can be seen that as the Ce content in the material environment increases, the plasma effect weakens, and the absorption value of the UV-vis spectrum decreases accordingly.
[0047] In addition, the photocatalytic performance of gold nanorods (Au NRs-80), gold-palladium bimetallic nanocuboid structures (Au@Pd NCBs-200), and ceria-coated gold-palladium bimetallic nanocuboid composite structures (Au@Pd@CeO2 NCBs-5) in reducing methylene blue (MB) to colorless methylene blue, i.e., reduced methylene blue (LMB) under xenon lamp light source was studied. 5 mL of Au@Pd@CeO2 NCBs-5 was centrifuged at 5000 r / min for 3 min and concentrated to 1 mL for photocatalytic performance test. 1 mL of concentrated Au@Pd@CeO2 NCBs-5 solution, 50 μL of sodium hydroxide with a molar concentration of 0.1 mol / L, 200 μL of methylene blue with a molar concentration of 0.5 mmol / L, and 3.75 mL of ultrapure water were mixed at room temperature to prepare a photocatalytic experimental solution. A fixed irradiance of 150 mW / cm 2The reaction mixture was irradiated with a xenon lamp light source. Subsequently, 150 μL of the reaction mixture was taken into the cuvette of the UV-2600 spectrometer every 3 minutes, and the spectrum was detected in real time. In the comparative experiment, the same centrifugal concentration treatment and photocatalytic experimental steps were also performed on Au NRs-80 and Au@Pd NCBs-200. At the same time, 1 mL of Au@Pd@CeO2 NCBs-5 was dried at 100°C, and a comparative experiment was performed on 1 mL of undried Au@Pd@CeO2 NCBs-5. The conversion of MB to LMB in the wavelength range of 300 to 900 nm was monitored by UV-visible spectroscopy.
[0048] Figure 5 The photocatalytic degradation effect of gold nanoparticles (Au NRs-80), gold-palladium bimetallic nanocube composite structure (Au@Pd NCBs-200), and core-shell gold-palladium bimetallic nanocube / cerium dioxide composite material (Au@Pd@CeO2 NCBs-5) on methylene blue before and after drying is shown. Figure 5 (a)-(d) are the UV-vis spectra of the photocatalytic degradation of methylene blue by Au NRs-80, Au@Pd NCBs-200 and Au@Pd@CeO2 NCBs-5 before and after drying. By comparing the characteristic peak of methylene blue at 665nm, it can be clearly seen that the Au@Pd@CeO2 NCBs-5 material has a significant photocatalytic degradation effect on methylene blue, and the degradation efficiency is higher after the material is dried within 24 minutes. Figure 5 (e)-(f) are the ln(C t The curve of (C0) versus time t is shown in Figure 2, and the fitting curve conforms to the first-order kinetic equation of the catalytic degradation of methylene blue.
Claims
1. A method for preparing a ceria-coated gold-palladium bimetallic nanocuboid composite material, characterized in that: The structure of the ceria-coated gold-palladium bimetallic nanocuboid composite material comprises: a gold-palladium bimetallic nanocuboid composite structure as a core and ceria as a shell layer. The specific preparation method comprises the following steps: (1) mixing hexadecyltrimethylammonium bromide, sodium oleate and ultrapure water and heating until all solids are dissolved to obtain a transparent colorless growth solution I; (2) cooling the growth solution I obtained in step (1), adding silver nitrate solution and chloroauric acid solution in sequence, stirring at a constant temperature, to obtain a mixed solution; (3) adding a sodium borohydride solution and a chloroauric acid solution to a hexadecyltrimethylammonium bromide solution in sequence, reacting in an ice bath to obtain a gold seed solution, and aging the gold seed solution to obtain gold seeds required for synthesizing gold nanorods; (4) adding hydrochloric acid, ascorbic acid solution and the gold seeds obtained in step (3) to the mixed solution obtained in step (2) in sequence under stirring, and after all the addition is completed, standing at a constant temperature to form a gold nanorod stock solution, centrifuging the gold nanorod stock solution to obtain a precipitate, and adding ultrapure water to the precipitate to obtain a gold nanorod concentrated solution; (5) mixing the hexadecyltrimethylammonium bromide solution, the ascorbic acid solution and the gold nanorod concentrate obtained in step (4) at a constant temperature to prepare growth solution II; (6) adding sodium chloropalladate solution to the growth solution II, stirring at a constant temperature and then standing to obtain a gold-palladium bimetallic nanocuboid composite structure stock solution, centrifuging the gold-palladium bimetallic nanocuboid composite structure stock solution, retaining the precipitate, and adding ultrapure water to the precipitate to obtain a gold-palladium bimetallic nanocuboid composite structure concentrated solution; (7) Adding ethylenediaminetetraacetic acid solution and cerium nitrate solution to the concentrated solution of gold-palladium bimetallic nanocuboid composite structure obtained in step (6) in sequence, and drying the obtained mixed solution to obtain cerium dioxide-coated gold-palladium bimetallic nanocuboid composite material.
2. The method for preparing the ceria-coated gold-palladium bimetallic nanocuboid composite material according to claim 1, characterized in that: In the step (1) ultrapure water, the amount of cetyltrimethylammonium bromide added is 9.1-37 g / L, the amount of sodium oleate added is 1-10 g / L, the molar ratio of cetyltrimethylammonium bromide to sodium oleate is 1:1-1:2, and the heating temperature is 30-90°C.
3. The method for preparing the ceria-coated gold-palladium bimetallic nanocuboid composite material according to claim 1, characterized in that: In step (2), the volume ratio of the growth solution I, the silver nitrate solution and the chloroauric acid solution is: (5-25): (1-4): (10-50); the molar concentration of the silver nitrate solution is 4-40 mmol / L, and the molar concentration of the chloroauric acid solution is 1-5 mmol / L; the temperature of the growth solution I after cooling is 20-40° C.; the temperature of the constant temperature stirring is 20-40° C., the stirring condition is 200-1000 r / min, and the stirring is 10-150 min.
4. The method for preparing the ceria-coated gold-palladium bimetallic nanocuboid composite material according to claim 1, characterized in that: In step (3), the volume ratio of the sodium borohydride solution, the chloroauric acid solution and the hexadecyltrimethylammonium bromide solution is 1:5:5, wherein the molar concentration of the sodium borohydride solution is 6 mmol / L, the molar concentration of the chloroauric acid solution is 0.5 mmol / L, and the molar concentration of the hexadecyltrimethylammonium bromide solution is 0.2 mol / L; the aging temperature is 25-50° C., and the aging time is more than 30 min.
5. The method for preparing the ceria-coated gold-palladium bimetallic nanocuboid composite material according to claim 1, characterized in that: In step (4), the amount of hydrochloric acid added to the mixed solution is 1-5 μL / ml, the amount of ascorbic acid solution added is 1-5 μL / ml, and the amount of gold seeds added is 0.35-1.4 μL / ml; the mass concentration of the hydrochloric acid is 37%, and the molar concentration of the ascorbic acid solution is 64-100 mmol / L.
6. The method for preparing the ceria-coated gold-palladium bimetallic nanocuboid composite material according to claim 1, characterized in that: In step (4), each reagent needs to be stirred for more than 30 seconds after addition, and the constant temperature is 20-40°C for a standing time of more than 12 hours; centrifugation is performed twice, and the centrifugation conditions are 6000-12000r / min for 2-10 minutes. After each centrifugation, the supernatant is removed and the precipitate is collected; the amount of ultrapure water used in the precipitate is 1 / 10 of the volume of the gold nanorod stock solution. times.
7. The method for preparing the ceria-coated gold-palladium bimetallic nanocuboid composite material according to claim 1, characterized in that: Step (5) In the growth solution II, the volume ratio of the hexadecyltrimethylammonium bromide solution, the ascorbic acid solution and the gold nanorod concentrate is (0.2-2):(0.2-2):(0.2-2), the molar concentration of the hexadecyltrimethylammonium bromide is 0.1-0.2 mol / L, and the molar concentration of the ascorbic acid is 0.064-0.1 mol / L; The constant temperature condition is 30℃.
8. The method for preparing the ceria-coated gold-palladium bimetallic nanocuboid composite material according to claim 1, characterized in that: In step (6), the amount of sodium chloropalladate solution added to the growth solution II is 16.7-50 μL / ml, the molar concentration of the sodium chloropalladate solution is 1-10 mmol / L, the constant temperature condition is 30° C., the stirring time is 5-10 min, and the standing time is 6-20 h.
9. The method for preparing the ceria-coated gold-palladium bimetallic nanocuboid composite material according to claim 1, characterized in that: The centrifugal condition in step (6) is 4000-10000r / min for 10-3min, and the amount of ultrapure water added to the precipitate is 1 / 10 of the volume of the gold-palladium bimetallic nanocuboid composite structure stock solution. times.
10. The method for preparing the ceria-coated gold-palladium bimetallic nanocuboid composite material according to claim 1, characterized in that: In step (7), the volume ratio of the gold-palladium bimetallic nanocuboid composite structure concentrated solution, the ethylenediaminetetraacetic acid solution and the cerium nitrate solution is 1:3.5:0.035-1:7:0.70, the molar concentration of the ethylenediaminetetraacetic acid solution is 1-10 mmol / L, and the molar concentration of the cerium nitrate solution is 10-100 mmol / L; the drying condition is 90-100° C. for 2-10 hours.